An API-Driven Framework for Performance Testing of Hyperledger Besu Blockchain Networks - Cardoso, Carlos; Silva, Caio; Veloso, Alan; Sousa, Jeffson; Abelém, Antônio (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC), 2025)
As Distributed Ledger Technologies (DLTs) mature into production-grade systems, a critical gap emerges between protocol-level benchmarking and application-centric performance testing. While specialized tools like Hyperledger Caliper excel at measuring core on-chain metrics, they are less suited for evaluating the end-to-end performance of applications that interact with the DLT through an intermediary API layer. This paper addresses this gap by proposing a three-tier, API-driven framework that enables mature, general-purpose load testing tools, such as Apache JMeter, to realistically assess a Hyperledger Besu network’s performance from an application’s perspective. The core of our solution is a custom API server that provides essential services like atomic nonce management and dynamic load balancing. Our comparative analysis demonstrates that while Caliper may report higher end-to-end throughput under specific conditions, our framework induces a significantly more substantial and evenly distributed load, revealing a more accurate picture of the network’s true processing capacity. Furthermore, our approach captures API-layer latency—a crucial metric for client-perceived responsiveness—which proved to be an order of magnitude lower than the on-chain finality measured by Caliper. This work validates a reusable architectural pattern for testing DLTs within a realistic application stack, bridging the gap between protocol benchmarking and real-world performance engineering.